The Socioeconomic Conditions and Behavior of Riverside Communities in Disposing of Waste in the Cisadane River Segment of South Tangerang City - Izzati, Urfi; Hasibuan, Hayati Sari (Monas: Jurnal Inovasi Aparatur, 2024)
The existence of settlements along riverbank, particularly in urban areas, can disrupt both the function of the river and its riverbank. The behavior of riverside communities generally adds to burden the river, primarily through the practice of disposing waste into the river and its riverbank. This behavior can cause detrimental effects on both the environment and society. This research aims to examine the socioeconomic conditions and waste disposal behavior of communities residing along the Cisadane River, South Tangerang City. This research is a quantitative descriptive study. Data collection involved the use of questionnaires, interviews, and observations, which were subsequently analyzed using descriptive statistical techniques. The findings revealed that the majority of riverside communities in South Tangerang City exhibited a high level of understanding (54.55%), a relatively positive perspective (75.76%), and a poor economic condition (57.58%). However, their waste disposal behavior was predominantly inadequate (51.52%). Consequently, the study indicates a discrepancy between the community's level of understanding, perspective, and actual waste disposal practices. With the intervention of communication forums, the creation of mutually agreed norms, and the availability of waste disposal and processing infrastructure, it is hoped that the community awareness and sense of responsibility would be enhanced, that will lead to no rubbish throwing into the river and its borders hence diminishing the burden of the river so that the function of the river and its borders are preserved.